SALIVARY IL-6 AND IL-8 AS POTENTIAL BIOMARKERS FOR ORAL SQUAMOUS CELL CARCINOMA - Bakti, Fitrah Utari; Setiadhi, Riani (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2023)
Introduction: Early identification of oral squamous cell carcinoma (OSCC) is a crucial factor influencing the disease's prognosis. The elevated levels of IL-6 and IL-8 in saliva are a result of their overproduction in the cancer microenvironment. The production of salivary cytokines, particularly IL-6 and IL-8, has a role in cancer development. These cytokines may also be used as biomarkers. The use of saliva as a biomarker is quite interesting because it is in direct contact with cancer cells, easy to access, non-invasive, and cost-effective. Aim: The aim of this literature review was to assess the potential of salivary IL-6 and IL-8 as biomarkers for OSCC early diagnosis. Review: The initiation of carcinogenesis in the oral cavity is actively repressed by inflammation and cell-mediated immunity. IL-6 and IL-8 are two important molecules involved in stromal-to-cancer cell communication. These cytokines play a major part in the growth, progression, metastasis, and recurrence of OSCC. Several studies have found that OSCC patients have higher levels of salivary IL-6 and IL-8 than healthy people and patients with an oral potentially malignant disorder (OPMD). Conclusion: Salivary IL-6 and IL-8 are very promising potential biomarkers for the early diagnosis of OSCC. Further research is still needed to validate and use these biomarkers clinically.